2002
DOI: 10.2466/pms.2002.94.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Traditional Judo Training on Aggressiveness among Young Boys

Abstract: This study assessed the effect of one year of traditional judo training on aggressiveness among young boys. 27 primary school pupils and 28 judo students were asked to complete the Buss-Perry Aggression Questionnaire at two times 1 year apart. Analysis showed that judoka were more aggressive (had higher scores on Total Aggression, Verbal Aggression, and Anger) than the control group after one year of training, even if variations in aggressiveness were not significant. So, results do not support the view that j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 10 publications
0
18
0
4
Order By: Relevance
“…Esto ha llevado a un creciente interés por acercase al campo de estudio de estas modalidades deportivas por parte de investigadores de todo el mundo (Vertonghen y Theeboom, 2010). Los beneficios psicológicos de su práctica han sido muy discutidos a lo largo de los años (Vertonghen y Theeboom, 2010), a pesar de que diferentes investigaciones han reportado tanto resultados negativos (Reynes y Lorant, 2002) como positivos (McDiarmid, 2007;Theeboom y De Knop, 1999).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Esto ha llevado a un creciente interés por acercase al campo de estudio de estas modalidades deportivas por parte de investigadores de todo el mundo (Vertonghen y Theeboom, 2010). Los beneficios psicológicos de su práctica han sido muy discutidos a lo largo de los años (Vertonghen y Theeboom, 2010), a pesar de que diferentes investigaciones han reportado tanto resultados negativos (Reynes y Lorant, 2002) como positivos (McDiarmid, 2007;Theeboom y De Knop, 1999).…”
Section: Introductionunclassified
“…Las variables psicológicas que se han estudiado dentro del campo de las AAMM y DDCC han sido muy diversas: ansiedad (Marks, Bukowska y Biéc, 2012), inteligencia emocional (Szabo y Urbán, 2014), resolución de conflictos (Björkqvist y Varhama, 2001), hostilidad (Daniels y Thornton, 1990) y especialmente, agresividad (Adler, 2003; Ali, Emrah, Fahri, Necmettin y Gülcan, 2010; Endresen y Olweus, 2005). La ira también ha sido otra variable objeto de análisis (Foster, 1997; Oliva y Calleja, 2010; Steyn y Roux, 2009) aunque tradicionalmente se ha estudiado a partir del constructo irahostilidad-agresión sin atender a la multidimensionalidad de esta emoción (Reynes y Lorant, 2001, 2002, 2004. En los últimos años ha crecido el número de trabajos que han explorado esta variable desde un prisma multidimensional, tanto en el ámbito de las AAMM y DDCC como en el del deporte en general (Bolgar, Janelle y Giaccobbi, 2008; Dunn, Gotwals, Causgrove, Dunn y Syrotuik, 2006; Oliva y Hernández, 2009; Oliva, Calleja y Hernández, 2011, 2012; Robazza, Bertollo y Bortoli, 2006; Ruiz y Hanin, 2011).…”
Section: Introductionunclassified
“…In their study, there was no significant difference between girls and boys [3]. In another study by these same researchers, carried out after one year of judo training, it was shown that judoka had significantly higher scores in total aggression, verbal aggression, and anger than the control group, indicating that differences were not based on differences among initial anger scores [9]. After a 2-year follow-up, they reported that judo training seemed to have a negative effect on anger scores [10].…”
Section: Discussionmentioning
confidence: 99%
“…They reported the absence of a significant difference in aggression scores of 8-year-old boys at the beginning of karate training when compared to their peers [3]. In their followup, after one year of traditional judo training, it was shown that judoka became more aggressive while after one year of karate training no significant change of aggressiveness was found [9, 11]. After two years of martial arts training, Reynes and Lorant reported that karate had no effect on aggressiveness while judo had a negative effect on anger scores [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation